Friars, Nobles and Burghers - Sermons, Images and Prints. - Miller, Jaroslav (JSTOR EBA., 2010)
The essays in this volume reflect the broader interpretation of culture as a system of shared meanings, values, attitudes and symbolic forms in any sphere of human life. Although thematically diverse, all these studies adhere to the concept of what is sometimes termed the new cultural history or socio-cultural history. The work opens with a cluster of methodological and historiographical reflections. Topics covered by the thematic sections include confessional and religious life in early modern Europe, symbolism and representation, strife and accommodation among different denominations compell.